Dynamic Responses of Semi-Submersible: A Comparison of Long-Crested and Short-Crested Waves with Current - Sok Jin, Ng (IRC, 2015)
As the development of oil and gas industry has progressed into deep-water, the study on deep-water offshore structures has become more important. Among the environmental force acting on the structures, wave forces are the most significant. Waves can be categorized as short-crested waves and long-crested waves based on the direction of propagation. Long-crested waves can be defined as two-dimensional waves, which extend infinitely in lateral direction. On the other hand, short-crested waves consist of a series of long-crested waves with random magnitude and directions in three-dimensional. It is more common to find short-crested waves in the real sea state instead of long-crested waves. Furthermore, no research has been performed on semi-submersible particularly focusing on short-crested waves and current concurrently. Therefore, the study to determine the dynamic responses of one of the deep-water offshore structures, i.e. semi-submersible platforms subjected to short-crested waves and current is more significant. In this study, a numerical comparative study on a typical eight-column semi-submersible model subjected to long-crested and short-crested waves with current had been conducted. In the research, frequency domain method, which adopted the Morison Equation and wave energy spectrum was utilized to obtain the responses in three degrees of freedom i.e. surge, heave, and pitch motion in term of Response Amplitude Operator (RAO). Besides, the maximum amplitude of each motion response was determined and compared. The results indicated that the dynamic responses for short-crested waves are approximately 50% lower than long-crested waves and the effect of current induced is insignificant.